Page 3 of 7 FirstFirst 1234567 LastLast
Results 31 to 45 of 105

Math Help - Limit Marathon

  1. #31
    Eater of Worlds
    galactus's Avatar
    Joined
    Jul 2006
    From
    Chaneysville, PA
    Posts
    3,001
    Thanks
    1
    Yep. That's it. Good job. It is easy if you spot it. Those are the fun ones.
    Follow Math Help Forum on Facebook and Google+

  2. #32
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Here is one, have fun with the simplicity

    \lim_{\psi\to{0^{+}}}\frac{\sin(\sqrt{\psi})\tan(e  ^{10\psi}-1)}{\sqrt{15\psi^8-17\psi^3+64\psi}}
    Follow Math Help Forum on Facebook and Google+

  3. #33
    Forum Admin topsquark's Avatar
    Joined
    Jan 2006
    From
    Wellsville, NY
    Posts
    10,212
    Thanks
    419
    Awards
    1
    Quote Originally Posted by galactus View Post
    \lim_{n\to\rightarrow{\infty}}\frac{1}{n}\sum_{j=1  }^{n}\sum_{k=1}^{n}\frac{j}{j^{2}+k^{2}}
    It would seem that this is 0 by a "power counting" argument. But I am having some trouble justifying it Mathematically.

    -Dan
    Follow Math Help Forum on Facebook and Google+

  4. #34
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by Mathstud28 View Post
    Here is one, have fun with the simplicity

    \lim_{\psi\to{0^{+}}}\frac{\sin(\sqrt{\psi})\tan(e  ^{10\psi}-1)}{\sqrt{15\psi^8-17\psi^3+64\psi}}
    hint
    ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
    Follow Math Help Forum on Facebook and Google+

  5. #35
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by Mathstud28 View Post
    Here is one, have fun with the simplicity

    \lim_{\psi\to{0^{+}}}\frac{\sin(\sqrt{\psi})\tan(e  ^{10\psi}-1)}{\sqrt{15\psi^8-17\psi^3+64\psi}}
    This actually turns out to be really easy

    Let u(0)=0

    Then \lim_{x\to{0}}\frac{\tan(u(x))}{u(x)}=1

    This can be done by making the sub with \psi=u(x)

    \therefore\tan(u(x))\sim{u(x)} if u(0)

    and the sine case was listed earlier, the other case can be seen before which states that if

    a polynomial approaches zero then it is ~ to its lowest powered x term

    \therefore\sqrt{15x^8-17x^3+64x}\sim{8\sqrt{x}}

    \therefore\lim_{\psi\to{0^{+}}}\frac{\sin(\sqrt{\p  si})\tan(e^{10\psi}-1)}{\sqrt{15\psi^8-17\psi^3+64\psi}}\sim\lim_{\psi\to{0^{+}}}\frac{\s  qrt{\psi}(e^{10\psi}-1)}{8\sqrt{\psi}}=0
    Follow Math Help Forum on Facebook and Google+

  6. #36
    MHF Contributor

    Joined
    May 2008
    Posts
    2,295
    Thanks
    7
    Quote Originally Posted by galactus View Post
    \lim_{n\to\infty}\frac{1}{n}\sum_{j=1}^{n}\sum_{k=  1}^{n}\frac{j}{j^{2}+k^{2}}
    nice problem! the sum is a double Riemann sum of f(x,y)=\frac{x}{x^2+y^2} on the unit square:

    \lim_{n\to\infty} \frac{1}{n}\sum_{j=1}^n \sum_{k=1}^n \frac{j}{j^2 + k^2}= \lim_{n\to\infty} \frac{1}{n^2} \sum_{j=1}^n\sum_{k=1}^n \frac{\frac{j}{n}}{(\frac{j}{n})^2 + (\frac{k}{n})^2}=\int_0^1 \int_0^1 \frac{x}{x^2 + y^2} \ dx \ dy

    =\frac{1}{2}\int_0^1 (\ln(y^2 + 1) - 2\ln y) \ dy=\frac{\pi}{4} + \frac{\ln 2}{2}. \ \ \ \square
    Last edited by NonCommAlg; June 10th 2008 at 03:47 PM.
    Follow Math Help Forum on Facebook and Google+

  7. #37
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Here are two simple ones


    \lim_{x\to{0}}\bigg[e^{\frac{5}{x}}-3x\bigg]^{\frac{x}{2}}

    and

    \lim_{x\to{0}}\frac{\sqrt{\cos(ax)}-\sqrt{\cos(bx)}}{x^2}
    Follow Math Help Forum on Facebook and Google+

  8. #38
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by Mathstud28 View Post
    Here are two simple ones


    \lim_{x\to{0}}\bigg[e^{\frac{5}{x}}-3x\bigg]^{\frac{x}{2}}

    and

    \lim_{x\to{0}}\frac{\sqrt{\cos(ax)}-\sqrt{\cos(bx)}}{x^2}

    Well I am sure there is a better way, but based one mine

    Hint: make a substitution

    Hint:conjugate
    Follow Math Help Forum on Facebook and Google+

  9. #39
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by Mathstud28 View Post
    Here are two simple ones


    \lim_{x\to{0}}\bigg[e^{\frac{5}{x}}-3x\bigg]^{\frac{x}{2}}

    and

    \lim_{x\to{0}}\frac{\sqrt{\cos(ax)}-\sqrt{\cos(bx)}}{x^2}
    For the first one

    \lim_{x\to{0}}\bigg[e^{\frac{5}{x}}-3x\bigg]^{\frac{x}{2}}


    First I let

    L=\lim_{x\to\infty}\bigg[e^{\frac{5}{x}}-3x\bigg]^{\frac{x}{2}}\Rightarrow{L^2}=\lim_{x\to\infty}\b  igg[e^{\frac{5}{x}}-3x\bigg]^{x}


    I then made the sub, let \psi=\frac{1}{x}

    so as x\to{0}\Rightarrow\psi\to\infty

    So we have that x=\frac{1}{\psi}

    So by subbing we have

    L^2=\lim_{\psi\to\infty}\bigg[e^{5\psi}-\frac{3}{\psi}\bigg]^{\frac{1}{\psi}}

    Now there are a few ways this could have been done, but the easiest is the Root/Ratio laws test trick

    \lim_{\psi\to\infty}\bigg[e^{5\psi}-\frac{3}{\psi}\bigg]^{\frac{1}{\psi}}=\lim_{\psi\to\infty}\frac{e^5\cd  ot{e^{5\psi}}-\frac{3}{\psi+1}}{e^{5\psi}-\frac{3}{\psi}}

    which then by termwise division gives

    \lim_{\psi\to\infty}\frac{e^5-\frac{3}{(\psi+1)e^{5\psi}}}{1-\frac{3}{\psi\cdot{e^{5\psi}}}}=e^5

    So L^2=e^{5}\Rightarrow{L=e^{\frac{5}{2}}}

    For our second limit

    multiplying by the conjugate gives

    \lim_{x\to{0}}\frac{\cos(ax)-\cos(bx)}{x^2\bigg[\sqrt{\cos(ax)}+\sqrt{\cos(bx)}\bigg]}

    Now by breaking it up we get

    \lim_{x\to{0}}\frac{\cos(ax)-\cos(bx)}{x^2}\cdot\lim_{x\to{0}}\frac{1}{\sqrt{\c  os(ax)}+\sqrt{\cos(bx)}}=\lim_{x\to{0}}\frac{\cos(  ax)-\cos(bx)}{2x^2}

    now seeing that

    \cos(ax)-\cos(bx)=\bigg[1-\frac{a^2x^2}{2}+\frac{a^4x^4}{24}-...\bigg]-\bigg[1-\frac{b^2x^2}{2}+\frac{b^4x^4}{24}-...\bigg]

    Grouping we get

    \cos(ax)-\cos(bx)=\bigg[1-1\bigg]+\frac{b^2-a^2}{2}x^2-\frac{b^4+a^2}{24}x^4+...\sim\frac{b^2-a^2}{2}x^2

    So then we have that

    \lim_{x\to{0}}\frac{\sqrt{\cos(ax)}-\sqrt{\cos(bx)}}{x^2}=\lim_{x\to{0}}\frac{\cos(ax)-\cos(bx)}{2x^2}\sim\lim_{x\to{0}}\frac{\frac{b^2-a^2}{2}x^2}{2x^2}=\frac{b^2-a^2}{4}
    Follow Math Help Forum on Facebook and Google+

  10. #40
    Moo
    Moo is offline
    A Cute Angle Moo's Avatar
    Joined
    Mar 2008
    From
    P(I'm here)=1/3, P(I'm there)=t+1/3
    Posts
    5,618
    Thanks
    6
    Hi,

    I've got a question for \left(e^{\frac 5x}-3x\right)^{\frac x2}

    Assuming that x tends to 0 from the right (>0), \frac 5x \to +\infty \implies e^{\frac 5x} \to +\infty, while 3x \to 0.

    So we can neglect 3x with regard to e^{\frac 5x}

    Therefore, the limit is \left(e^{\frac 5x}\right)^{\frac x2}=e^{\frac 52}


    Also, I think you should be patient, we're not all in the same GMT and we're not as available as you are. So if no one answers within 2 hours, it's not a catastrophe...
    Follow Math Help Forum on Facebook and Google+

  11. #41
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by Moo View Post
    Hi,

    I've got a question for \left(e^{\frac 5x}-3x\right)^{\frac x2}

    Assuming that x tends to 0 from the right (>0), \frac 5x \to +\infty \implies e^{\frac 5x} \to +\infty, while 3x \to 0.

    So we can neglect 3x with regard to e^{\frac 5x}

    Therefore, the limit is \left(e^{\frac 5x}\right)^{\frac x2}=e^{\frac 52}


    Also, I think you should be patient, we're not all in the same GMT and we're not as available as you are. So if no one answers within 2 hours, it's not a catastrophe...
    Haha thanks for pointing that out, I fixed that, if you look back I just literally stopped. I went and made a sandwich and when I came back I started on the second and didnt finish the first

    As for thse second one

    So if no one answers within 2 hours, it's not a catastrophe...
    Yes it is
    Follow Math Help Forum on Facebook and Google+

  12. #42
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Ok, here are two more

    This first one I did yesterday on another website, so if you have seen it, dont spoil it..not that its that hard

    \lim_{x\to{0}}\frac{a^{x^2}-\cos(x)}{\sin(x^2)}

    and the other is

    \lim_{n\to\infty}\bigg(\frac{3^n+5^n}{2^n+5^n}\big  g)^{n(\sqrt{n+1}-\sqrt{n})}
    Follow Math Help Forum on Facebook and Google+

  13. #43
    Super Member PaulRS's Avatar
    Joined
    Oct 2007
    Posts
    571
    Quote Originally Posted by Mathstud28 View Post
    \lim_{x\to{0}}\frac{\sqrt{\cos(ax)}-\sqrt{\cos(bx)}}{x^2}
    Just note that: <br />
\frac{{\sqrt {\cos \left( {ax} \right)}  - \sqrt {\cos \left( {bx} \right)} }}<br />
{{x^2 }} =  - \tfrac{1}<br />
{{2x}} \cdot \int_b^a {\tfrac{{\sin \left( {x \cdot y} \right)}}<br />
{{\sqrt {\cos \left( {x \cdot y} \right)} }}dy} <br />

    <br />
\mathop {\lim }\limits_{x \to 0} \frac{{\sqrt {\cos \left( {ax} \right)}  - \sqrt {\cos \left( {bx} \right)} }}<br />
{{x^2 }} =  - \tfrac{1}<br />
{2} \cdot \mathop {\lim }\limits_{x \to 0} \int_b^a {\tfrac{{\sin \left( {x \cdot y} \right)}}<br />
{{x \cdot \sqrt {\cos \left( {x \cdot y} \right)} }}dy}  = <br />
<br />
 - \tfrac{1}<br />
{2} \cdot \int_b^a {\mathop {\lim }\limits_{x \to 0} \tfrac{{\sin \left( {x \cdot y} \right)}}<br />
{{x \cdot \sqrt {\cos \left( {x \cdot y} \right)} }}dy}  =  - \tfrac{1}<br />
{2} \cdot \int_b^a {y \cdot dy} <br />
(assuming uniform convergence)

    Thus: <br />
\mathop {\lim }\limits_{x \to 0} \frac{{\sqrt {\cos \left( {ax} \right)}  - \sqrt {\cos \left( {bx} \right)} }}<br />
{{x^2 }} = \tfrac{{b^2  - a^2 }}<br />
{4}<br />
    Follow Math Help Forum on Facebook and Google+

  14. #44
    Super Member PaulRS's Avatar
    Joined
    Oct 2007
    Posts
    571
    Quote Originally Posted by Mathstud28 View Post
    \lim_{x\to{0}}\frac{a^{x^2}-\cos(x)}{\sin(x^2)}
    L=\mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 }  - \cos \left( x \right)}}<br />
{{\sin \left( {x^2 } \right)}} = \mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 }  - 1 + 1 - \cos \left( x \right)}}<br />
{{\sin \left( {x^2 } \right)}}<br />

    Now: <br />
\sin \left( {x^2 } \right)\mathop  \sim \limits_{x \to 0} x^2 <br />
and we'll split the limit in 2 parts since both are defined.

    <br />
L = \mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 }  - 1}}<br />
{{x^2 }} + \mathop {\lim }\limits_{x \to 0} \tfrac{{1 - \cos \left( x \right)}}<br />
{{x^2 }}<br />

    And: <br />
\left\{ \begin{gathered}<br />
  a^{x^2 }  - 1 = e^{x^2 \ln \left( a \right)}  - 1\mathop  \sim \limits_{x \to 0} x^2 \ln \left( a \right) \hfill \\<br />
  1 - \cos \left( x \right)\mathop  \sim \limits_{x \to 0} \tfrac{{x^2 }}<br />
{2} \hfill \\ <br />
\end{gathered}  \right.<br />

    So we get: <br />
L = \ln \left( a \right) + \tfrac{1}<br />
{2}<br />
    Follow Math Help Forum on Facebook and Google+

  15. #45
    MHF Contributor Mathstud28's Avatar
    Joined
    Mar 2008
    From
    Pennsylvania
    Posts
    3,641
    Quote Originally Posted by PaulRS View Post
    L=\mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 } - \cos \left( x \right)}}<br />
{{\sin \left( {x^2 } \right)}} = \mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 } - 1 + 1 - \cos \left( x \right)}}<br />
{{\sin \left( {x^2 } \right)}}<br />

    Now: <br />
\sin \left( {x^2 } \right)\mathop \sim \limits_{x \to 0} x^2 <br />
and we'll split the limit in 2 parts since both are defined.

    <br />
L = \mathop {\lim }\limits_{x \to 0} \tfrac{{a^{x^2 } - 1}}<br />
{{x^2 }} + \mathop {\lim }\limits_{x \to 0} \tfrac{{1 - \cos \left( x \right)}}<br />
{{x^2 }}<br />

    And: <br />
\left\{ \begin{gathered}<br />
a^{x^2 } - 1 = e^{x^2 \ln \left( a \right)} - 1\mathop \sim \limits_{x \to 0} x^2 \ln \left( a \right) \hfill \\<br />
1 - \cos \left( x \right)\mathop \sim \limits_{x \to 0} \tfrac{{x^2 }}<br />
{2} \hfill \\ <br />
\end{gathered} \right.<br />

    So we get: <br />
L = \ln \left( a \right) + \tfrac{1}<br />
{2}<br />
    I did it very similarly

    a^{x^2}-\cos(x)=e^{x^2\ln(a)}-\cos(x)=\bigg[1+\ln(a)x^2+\frac{\ln^2(a)x^4}{2}+...\bigg]-\bigg[1-\frac{x^2}{2}+\frac{x^4}{4!}-..\bigg]

    Combining we get

    a^{x^2}=\bigg[1-1\bigg]+\frac{2\ln(a)+1}{2}x^2+...\sim\bigg(\ln(a)+\frac{  1}{2}\bigg)x^2

    and \sin(x^2)=x^2-\frac{x^6}{3!}+\frac{x^{10}}{5!}-...\sim{x^2}

    \therefore\lim_{x\to{0}}\frac{a^{x^2}-\cos(x)}{x^2}\sim\lim_{x\to{0}}\frac{\bigg(\ln(a)+  \frac{1}{2}\bigg)x^2}{x^2}=\ln(a)+\frac{1}{2}
    Follow Math Help Forum on Facebook and Google+

Page 3 of 7 FirstFirst 1234567 LastLast

Similar Math Help Forum Discussions

  1. Secondary school's competition - marathon.
    Posted in the Math Topics Forum
    Replies: 4
    Last Post: August 30th 2010, 05:45 AM
  2. Limit, Limit Superior, and Limit Inferior of a function
    Posted in the Differential Geometry Forum
    Replies: 2
    Last Post: September 3rd 2009, 06:05 PM
  3. DE Marathon
    Posted in the Differential Equations Forum
    Replies: 26
    Last Post: July 21st 2008, 11:15 AM
  4. Small limit marathon
    Posted in the Calculus Forum
    Replies: 40
    Last Post: July 20th 2008, 10:40 PM
  5. Geometry Marathon
    Posted in the Geometry Forum
    Replies: 49
    Last Post: July 16th 2007, 02:44 PM

Search Tags


/mathhelpforum @mathhelpforum